Influencer Marketing and Engagement of Social Media Influencers: A Conceptual Paper - Mohd Khairulamiren; Amily Fikry Aziz (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Influencer marketing has been substantially adopted in the digital marketing strategy due to the rise of internet especially social media. This conceptual paper is aimed to study the relationship of social media influencers (SMIs) engagement and its influence on customers perceptions and behaviours from endorsed online brands. The study examines the attributes of the SMIs including attractiveness, expertise and trustworthiness, which are adopted from Source Credibility Theory. The data and methodology were gathered from previous articles in Web of Science (WoS) and Scopus databases. Content analysis from the articles was done to come out with the adopted theory and research framework. The results from the analysis found that strong relationship of the SMIs contribute to the increase of sale of products and services, as well as to motivate their audience to own the products and services by changing these customers’ perceptions. Attributes of the SMIs gives the strong perceptions to the customers, while acting as endorsement that everyone has to believe. Overall, positive attributes of the SMIs have positive influence on the customers perceptions and behaviours. Thus, this paper provide insights on how the credibility of the SMIs can be the major influence to customers behaviours while offering the businesses to consider this value when searching endorser for their products and services.